2017
DOI: 10.1101/gad.305441.117
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-dependent O-GlcNAc signaling drives liver autophagy in adaptation to starvation

Abstract: Starvation induces liver autophagy, which is thought to provide nutrients for use by other organs and thereby maintain whole-body homeostasis. Here we demonstrate that O-linked β-N-acetylglucosamine (O-GlcNAc) transferase (OGT) is required for glucagon-stimulated liver autophagy and metabolic adaptation to starvation. Genetic ablation of OGT in mouse livers reduces autophagic flux and the production of glucose and ketone bodies. Upon glucagon-induced calcium signaling, calcium/calmodulin-dependent kinase II (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
108
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(119 citation statements)
references
References 62 publications
9
108
2
Order By: Relevance
“…Mounting evidence suggests that IBD‐associated mutations in autophagy‐related genes impair Paneth cell function (Cadwell et al , ; Henckaerts et al , ; Patel & Stappenbeck, ; Chu et al , ). Consistent with our recent finding that protein O‐GlcNAcylation promotes hepatic autophagy (Ruan et al , ), pro‐LC3 was accumulated and failed to be cleaved and activated to form LC3‐II in the IEC of Vil‐Ogt KO mice (Fig D). These data indicate that loss of OGT causes Paneth cell dysfunction.…”
Section: Resultssupporting
confidence: 91%
“…Mounting evidence suggests that IBD‐associated mutations in autophagy‐related genes impair Paneth cell function (Cadwell et al , ; Henckaerts et al , ; Patel & Stappenbeck, ; Chu et al , ). Consistent with our recent finding that protein O‐GlcNAcylation promotes hepatic autophagy (Ruan et al , ), pro‐LC3 was accumulated and failed to be cleaved and activated to form LC3‐II in the IEC of Vil‐Ogt KO mice (Fig D). These data indicate that loss of OGT causes Paneth cell dysfunction.…”
Section: Resultssupporting
confidence: 91%
“…Previously, we have shown that OGT performs essential functions in liver physiology by regulating gluconeogenesis and the insulin signaling pathway (30,31), circadian clock (32), and autophagy (33). Germline OGT deletion is lethal at the embryogenesis stage.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies have examined the negative regulation of autophagy by insulin in the liver, little has been known about the mechanism(s) by which glucagon induces autophagy. A recent article in Genes & Development by Ruan et al provides new insights into glucagon regulation of hepatic autophagy during nutrient deprivation. The findings demonstrate a novel function for the protein modification of O‐linked β‐N‐acetylglucosamine (O‐GlcNAc) in the regulation of starvation‐induced autophagy through an effect on unc‐51‐like kinase 1 (ULK1), which initiates the process of phagophore formation …”
mentioning
confidence: 99%
“…The studies by Ruan et al specifically examined the role of the posttranslational protein modification in which O‐GlcNAc moieties are attached to serine or threonine residues. O‐GlcNAcylation had been implicated previously as a nutrient sensor .…”
mentioning
confidence: 99%